Formulation, Analysis and Estimation of DSGE Models - Šilhart, Marek (2021)
The objective of this diploma thesis is to derive canonical, medium scale DSGE model of New Keynesian economics and consequently estimate its parameters using Bayesian techniques. After that, dynamics and identification of estimated model is examined. The model contains all standard features of medium scale DSGE models like nominal and real rigidities, backward indexation of wages and prices, habit formation, etc. The estimated model shows strong price rigidity, the coefficient describing the degree of price rigidity is 0.97. On the other hand, the wage rigidity is very weak, 0.07. The relative risk aversion parameter was estimated to be 1.32 which implies intertemporal elasticity of substitution as big as 0.76. The model also shows strong backward indexation for both prices and wages - estimated parameters are 0.86 and 0.62 respectively. The estimated monetary policy rule suggests strong interest rate inertia. The autoregressive parameter at the lagged interest rate was estimated to value 0.92. The impulse response function to government spending shock implies a potential need to incorporate a heterogeneous, non-Ricardian consumer to fit the empirical findings better. The identification analysis indicated that all parameters were identified, but some seemed to be identified weakly, in comparison with others.